NMR approach for the authentication of 10 cinnamon spice accessions analyzed via chemometric tools. (April 2018) - Farag, Mohamed A.; Labib, Rola M.; Noleto, Clarice; Porzel, Andrea; Wessjohann, Ludger A.
Abstract: Quantitative NMR metabolomics approach was developed to distinguish two cinnamon species (Ceylon Cinnamon, Cinnamomum verum and Chinese Cinnamon, Cinnamomum cassia ) that are interchangeably used in food products. The results of the analyses of 10 bark accessions revealed for 9 key sensory metabolites, with ( E )-cinnamaldehyde as the major form. Multivariate data analyses revealed for eugenol leading presence in C. verum versus fatty acid enrichment in C. cassia . This research provides the first NMR metabolites fingerprinting of the two major cinnamon resources. Compounds related to C. verum aroma and taste were identified and quantified that can be utilized as markers for the authentication of this valuable drug. Novel insight on metabolites mediating for C. verum antidiabetic effect is also presented. Highlights: Metabolic profiling of 10 Cinnamon and Cassia accessions. Eugenol was found in most Cinnamon specimens. Quantification of 8 major flavor compounds. Chemometric authentication of Cinnamon drugs.